PENDAPATAN DAN KOMPARASI PETANI USAHATANI PADI SAWAH DENGAN MENGGUNAKAN TEKNOLOGI SISTEM TANAM JAJAR LEGOWO DAN KONVENSIONAL DI KABUPATEN KARAWANG - Ray Samwal Alfariqi; Dini Rochdiani; Eti Suminartika (Universitas Galuh Ciamis, 2021)
Increasing rice production through improvements on the production side is important to be implemented to achieve food sovereignty, resilience and self-sufficiency. Several government efforts to increase national rice production have been carried out. The research objective was to analyze the comparative income of farmers in lowland rice farming using the legowo row and conventional cropping system technology in Karawang district. The research design used a quantitative approach. This research was conducted in Karawang Regency, the sample of farmers in the legowo row and conventional cropping system technology was 110 farmers consisting of 50 farmers who used the jarwo planting system, and 60 farmers who used the conventional planting system. Cost analysis is done by grouping the costs used which consist of fixed costs and variable costs and different tests. The results of the research were farmers' income in lowland rice farming using the legowo row cropping system with an average value (Rp. 38,026,916.41 / ha / MT) from the conventional planting system (Rp. 28,118,602 / ha / MT). The comparison of lowland rice farming farmers' income based on different test analysis shows that there is a difference between the income of farmers in lowland rice farming that applies the legowo row planting system technology which is greater than conventional.